(untitled) - Tomova, Anna; Badanik, Benedikt (Doprava a spoje, 2012)
In this paper we analyse essential risks factors influencing success or failure in Public Private Partnerships implementations within infrastructure sectors. We introduce concrete examples of failured Public-Private Partnerships projects within the sectors as well as statistics of failured PPPs in transport, water and sewerage and energy sectors in middle and low income countries in the world using the Private Participation in Infrastructures database of the World Bank. We generalise conclusions about factors that predetermine long term vitality of PPPs being thus determinants of their development.